Designating of Processing Unit of Corn Tortilla Chips for Small Scale Industry - Kumalaningsih, Sri; Wignyanto, Wignyanto; Fitria, Fitria (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
This study was aimed at finding out the best proportion of soy flour and wheat flour needs to add in the making of corn-based tortilla chips and then used it to design a small scale industry producing such chips. A Completely Randomized Design experiment was carried out employing two factors i.e. proportion of soy flour and wheat flour respectively, at 3 levels each, and was conducted in triplicates. The results showed that an addition of 0% soy flour and 4% wheat flour was considered the best in production corn-based tortilla chips. It has a product value of 0.802, a moisture content of 4.088%, 0.710% free fatty acid, and the yield of 59.37%. Based on a production capacity of 50 kg product per day which was designed for 5 years of operation, the value of total investment needed is Rp 140,990,137.00. It was found that the production cost per unit was Rp 499.00. By defining a margin of 20%, the price of the product at a retailer level is about Rp 550.00 per unit, by assuming the consumersâ price of Rp 700.00 per unit. A break even point will be achieved at a level of production of 244,137 units of 30 gram or equal to 48.85% of its capacity operation. It means that by an operation level of 6 months a year, the unit is still able to survive. The calculated pay back periods is 3.76 years and a profitability index of 1.19. Â Keywords: Processing unit, corn tortilla chips